Catalytic oxidation of organic pollutants in aqueous solution using sulfate radicals - Sun, Hongqi; Wang, Shaobin (The Royal Society of Chemistry, 2015)
Industrial and academic scientists face increasing challenges to find cost-effective and environmentally sound methods for converting natural resources into fuels, chemicals, and energy. This series provides a balanced and in-depth review of the modern approaches to these challenges, covering major areas such as chemical transformations using two-dimensional hybrid nanocatalysts, catalytic conversion of CO2 and catalytic oxidation of organic pollutants in aqueous solution using sulfate radicals.